Transverse mode instability in passive fiber induced by stimulated raman scattering - Distler, Victor; Möller, Friedrich; Strecker, Maximilian; Walbaum, Till; Schreiber, Thomas; Tünnermann, Andreas (Optics InfoBase Conference Papers, 2020)
We observed SRS-induced transverse mode instabilities in passive fiber. This was achieved by using a high-power Ytterbium-doped fiber laser as pump for a Raman amplifier whose stability was measured at various fiber positions.
CRIS-Team Scopus Importer:2023-04-20